Development of an Anti-Bullying Insert Learning Model (IAB) in Pancasila Education Subject Class VII - Bidasari Permata Bunda; Azwar Ananda; Al Rafni; Fatmariza (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study aims to develop the Insert Anti-Bullying (IAB) Learning Model in Civics Education (Pendidikan Pancasila) within the topic of Indonesian Social Diversity at Grade VII of SMP Negeri 1 Panyabungan Selatan. The persistent phenomenon of bullying in schools demands a systematic and value-based pedagogical solution. Using a Research and Development (R&D) approach with the ADDIE model, this study produced a six-syntax instructional model integrating the five principles of Pancasila as the moral framework for bullying prevention. Expert validation for both content and instructional design achieved an average score of 3.75 (Very Valid). The Paired Sample t-Test yielded t = 18.742 with p = 0.000 (p < 0.05), proving a significant improvement in students' anti-bullying attitudes from a mean score of 51.00 (pretest) to 76.53 (posttest). An average N-Gain of 0.53 (Moderate) and practicality rate of 91.9% (Very Practical) confirm that the IAB model is valid, practical, and effective